2020
DOI: 10.1152/ajpregu.00288.2019
|View full text |Cite
|
Sign up to set email alerts
|

Role of glucocorticoid signaling in exercise-associated changes in high-fat diet preference in rats

Abstract: The simultaneous introduction of wheel running (WR) and diet choice (high-carbohydrate chow vs. high-fat diet) results in sex-specific diet choice patterns in rats. WR induces a high-fat (HF) diet avoidance, and such avoidance persists in the majority of males, but not females, throughout a 2-wk period. Exercise is a physiological stressor that activates the hypothalamic-pituitary-adrenal (HPA) axis and stimulates glucocorticoid (GC) release, which can alter dietary preferences. Here, we examined the role of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 87 publications
1
2
0
Order By: Relevance
“…While this crossover effect is influenced by exercise duration and intensity, it may partially contribute to differences in macronutrient preference among sedentary and physically active individuals. Our previous short-term studies with the same paradigm of wheel running and two-diet choice revealed that the majority of male rats express persistent HF diet avoidance whereas the majority of females reverse HF diet avoidance [80,[93][94][95]. These results are consistent with the report that estradiol enhances lipid metabolism during exercise in rats [96].…”
Section: Discussionsupporting
confidence: 89%
“…While this crossover effect is influenced by exercise duration and intensity, it may partially contribute to differences in macronutrient preference among sedentary and physically active individuals. Our previous short-term studies with the same paradigm of wheel running and two-diet choice revealed that the majority of male rats express persistent HF diet avoidance whereas the majority of females reverse HF diet avoidance [80,[93][94][95]. These results are consistent with the report that estradiol enhances lipid metabolism during exercise in rats [96].…”
Section: Discussionsupporting
confidence: 89%
“…Further studies have shown that chronic mild stress in rats leads to increased gene expression of GR and Sgk1 in the prefrontal cortex but not hippocampus, while Fkbp5 was increased in both regions (Wei et al., 2016). An 18‐day voluntary wheel running protocol has also been shown to increase Fkbp5 expression in the medial prefrontal cortex and hippocampus of female but not male rats (Yang et al., 2020). From the gene expression analysis, it is therefore unclear if the changes we have seen in our exercise rats indicate a level of stress or not.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has found an increase in the gene expression of FKBP5 in relevant limbic areas (e.g. mPFC, insular cortex and hippocampus) after a protocol of wheel-running [29,30]. It is possible that the enhancement of FKBP5 after running is induced by glucocorticoids (GCs) increase owing to the stressful, but positive, nature of aerobic exercise.…”
Section: The Unknown Role Of Fkbp5 Protein In the Positive Effects Induced By Aerobic Exercisementioning
confidence: 99%